Literature overview on P3 measurement as an objective measure of auditory performance in post-lingually deaf adults with a cochlear implant. (2nd December 2019) - Jacquemin, Laure; Mertens, Griet; Schlee, Winfried; Van de Heyning, Paul; Gilles, Annick
Abstract: Objective: Cochlear implantation results in restoration of hearing, potential cortical reorganisation and the reallocation of attentional resources to the auditory system. Hence, the distorted cortical activity of patients with profound sensorineural hearing loss may be partially reversed. The measurement of auditory event-related potentials (ERPs) forms a promising electrophysiological evaluation of the central auditory nervous system. In particular, the P3 component is hypothesised to be a differential indicator of subjective auditory discrimination. This overview discusses the association between the cortical P3 component and the performance on auditory tests in post-lingually deaf adults using a CI. Moreover, the current article proposes important guidelines on eliciting, recording and analysing ERPs in CI users. Design: The literature search was conducted in PubMed. Study sample: Articles were included if they focussed on the relationship between P3 and auditory performance of an adult CI population. Results: The higher-order processing of speech in quiet and in noise of adult CI users is correlated with the ERP components, including the P3, shedding light on neurophysiological foundations for auditory performance differences. Conclusions: There is a need for replicating studies with larger sample sizes to fully comprehend the relationship between P3 and the auditory performance of CI users.